Mapping Global Trends in Feminist Pedagogy: A Bibliometric Analysis - Novemy Dhita, Aulia; Supriatna, Nana; Saripudin, Didin; Wiyanarti, Erlina; Kurniawan, Dedi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study examines the global development of feminist pedagogy scholarship to highlight that gender equality remains a pressing concern, despite prevailing perceptions that women have achieved parity with men. The aim is to demonstrate how feminist pedagogy serves as a critical educational approach to address ongoing gender disparities, including those within classroom contexts. Method: A bibliometric analysis was conducted on 253 articles and reviews on feminist pedagogy published between 2004 and 2024 and indexed in the Scopus database. Data analysis employed VOSviewer and Microsoft Excel to identify the most influential authors, affiliations, and countries, and to map citation patterns and research networks. Results: Findings reveal a dominance of contributions from researchers in the United States, with notably lower participation from Asian countries and other regions. Despite these geographical disparities, feminist pedagogy consistently emerges as a transformative educational approach in combating gender discrimination and fostering inclusive learning environments, with teachers playing a pivotal role in its implementation. Novelty: This review underscores the enduring relevance of feminist pedagogy in education amid ongoing sexism, policy limitations, and cultural resistance. By integrating feminist pedagogy into educational practices, stakeholders can advance gender equality not only in schools but also in society at large, contributing to more equitable and inclusive global education systems.